Transformation and kinetics of chlorine-containing products during pyrolysis of plastic wastes. (December 2021) - Pan, Jing; Jiang, Hong; Qing, Taiping; Zhang, Junfeng; Tian, Ke
Abstract: Pyrolysis can not only effectively dispose of plastic wastes but also reclaim valuable chemicals and biochar. However, the production and release of second pollutants, particularly chlorine-containing products, have been neglected. The mechanism for the transformation of chlorine during the pyrolysis of plastic wastes remains unclear. Herein, a thermogravimetric Fourier transform infrared mass spectrometry technology was used to investigate the migration and transformation of substances during the pyrolysis of polyvinyl chloride (PVC) plastic from 200 °C to 900 °C with heating rates of 5, 50, 100, 150, and 200 K min −1 . Results show the first stage of weight loss is at 200 °C-360 °C, where the dehydrochlorination of PVC mainly occurred, accompanied by the formation of conjugated double bonds and a small number of hydrocarbon compounds. The second stage of weight loss is at 360 °C-550 °C, where the breakage and rearrangement of the long polyethene chain may occur. Kinetics analysis shows the higher activation energy value is in the second stage, which indicates that the second stage reaction is less likely to occur and the Flynn–Wall–Ozawa method is more suitable for the study of plastic pyrolysis kinetics. This study suggests that second pollutants can be minimized during controllable pyrolysis. Graphical abstract: Image 1 Highlights: The PVC plastic pyrolysis process was studied by TG-FTIR-MS. PVC plastic pyrolysis is mainly divided into two stages. Pyrolysis of PVC plastic was studied at different heating rates. FWO, KAS and FR methods were used to study plastic pyrolysis kinetics.